(untitled) (Linguist, 2025)
The essay we want to translate falls within the context of understanding and explaining the teacher’s action; The study of this action allows understanding the manner in which it produces its discourses and the ends that frame this production process. This essay seeks to conduct a pragmatic approach to didactical interactions, which leads to an examination of the notion of context, and to the clarification of the context-inference relationship. The authors of this essay, Gérard Sensevy and Serge Quilio, suggest that the teacher’s linguistic action is a product of institutions characterized by specific environments and specific contracts. These institutions produce logical images that provide certain inferences according to the nature of the situation. For this reason, Sensevy and Quilio will surround two mutually dependent properties of the linguistic action of the teacher, namely the principle of didactical restriction and perlocutionary valence. Two characteristics that characterize the teacher’s discourse will be dealt with by studying the teacher’s action in different disciplines.